Economic evaluation of the use of distillers dried grains with solubles in swine feeding (Research, Society and Development, 2021)
This study proposes to undertake an economic assessment of the inclusion of different levels of distillers dried grains with solubles (DDGS) in diets for pigs in different production stages and categories (growing and finishing), namely: barrows fed diets containing 0 or 20% DDGS; and finishing barrows and sows fed diets containing 0, 10, 20, and 30% DDGS. A sensitivity analysis was performed on the price of corn in three simulated scenarios with different revenue systems: an optimistic scenario (lowest price); a regular scenario (medium price); and a pessimistic scenario (highest price). Inclusion of DDGS in the swine diet can reduce feeding costs and improve the profitability of production, about finishing males and females, the profit per kilogram of weight gain (US$/kg) were better in 10% of DDGS inclusion, 0.23, 0.28 respectively, but for growing and finishing, it was smaller in 20% (0.32 US$/kg) of DDGS inclusion than the 0% control treatment (0.33 US$/KG). The inclusion of DDGS must be carefully planned, since its use may depress animal performance and its inclusion is linked to the costs of the other ingredients that make up the diet.